COMMUNICATION ANTHROPOLOGICAL AND VALUE BASICS: THEORETICAL AND PRACTICAL ASPECTS - M. V. Silantyeva; A. V. Shestopal (Концепт: философия, религия, культура, 2017)
The rapid development of social and humanitarian fields in modern times and the emergence of a large number of practically important areas in which the commitment to interdisciplinary approach is justified set the task to rethink the amount of theoretical conclusions that enable us to determine promising areas and boundaries of such cooperation. Conceptual model of anthropological and axiological approach (in the framework of philosophical comparativism) comes from a number of theoretical and methodological assumptions, suggesting to perform diverse cultures' "horizontal" (synchronous) and "vertical" (diachronic) comparative analysis aimed to optimize their interaction. Among its basic foundations are: first, attention to the spatial and temporal concepts at the level of everyday communication and culture's intellectual reflection on itself; secondly, the study of the moral, religious, and aesthetic canons and innovation, specific to certain socio-cultural environment; thirdly, the research of formats of intercultural interaction within targeted community in various spheres - from cultural exchanges to economic and political processes, expecting literature searches on the subject, as well as discussions with representatives of particular cultures and activities. Essentially, it refers to identifying linguocultural and behavioral patterns that express cultural forms typical for a particular country and region in the modern era; as well as to their relevant disclosures in real time. A separate task is to clarify the thesaurus through the understanding of discursive practices, including "reflexive use of the word" in "high" stylistic registers of science and philosophy that have an indirect impact on its everyday usage. This update is related to further development of categorical apparatus, taking into account the achievements of linguistics, cultural research, cognitive studies in various fields, and at the same time based on the immanent theoretical development of the conceptual frameworks of philosophy as a self-contained discipline. It is clear that the task suppose just provisional conclusion: proposed ideas need to be adjusted and enhanced by a wide range of professionals working in the field of intercultural communication, and should be constantly updated due to the the replenishment of the latest research data.